Figure-Eight Coils for Magnetic Stimulation: From Focal Stimulation to Deep Stimulation - Ueno, Shoogo; Sekino, Masaki (Frontiers in Human Neuroscience, 2021)
This article reviews the evolution and recent developments of transcranial magnetic brain stimulation using figure-eight coils to stimulate localized areas in the human brain. Geometric variations of figure-eight coils and their characteristics are reviewed and discussed for applications in neuroscience and medicine. Recent topics of figure-eight coils, such as focality of figure-eight coils, tradeoff between depth and focality, and approaches for extending depth, are discussed.